STATUS GIZI DAN STATUS KESEGARAN JASMANI PESERTA DIDIK SEKOLAH DASAR NEGERI BANUA PADANG KECAMATAN BUNGUR KABUPATEN TAPIN - Denker Sandra Amicetya (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2014)
Nutritional Status And The Status Of Physical Freshness Of Primary School   Learners   Banua   Districts   Of   The   Country,   Lagerstroemia   Tapin Regency.The  purpose  of  this  research  is  to  determine  the  nutritional  status  and statuswithkeseg ran physical SDN Banua Padang District of Bungur Regency of Tapin. Research  methods  used  in  this  research  is  quantitative  descriptive  technique  of measurement and test. Populasi in this research is SDN Banua Padang District of Bungur Regency  of  Tapin  Lagerstroemia.  Lagerstroemia  totalling  143  people.  The  research sample is learners classes V and VI which was 10-12 years amounted to 40 people. Sampling using the technique of sampling purpossive.Research results revealedthat overall nutritional status learners SDN Banua Padang District of Bungur Regency of Tapin. Lagerstroemia in the category either (B). D's to the status of physical freshness within the classification Being (S). Keywords: Nutritional Status, Status of Physical Freshness